Analysis of physical fitness and technical skills of youth soccer players according to playing position - Joo, Chang Hwa; Seo, Dong-Il (Journal of exercise rehabilitation, 2016)
The purpose of this study was to compare performance factors of youth soccer players according to position. A total of 101 high school soccer players were selected and were classified into goalkeeper (n=7), de-fense (n=37), midfield (n=39), and forward (n=18) positions. All sub-jects were subjected to the Wingate test for anaerobic capacity, shuttle run test for aerobic capacity, and pass, kick, dribble, and shooting tests for soccer skills. There was no significant difference in aerobic capaci-ty according to position. However, anaerobic capacity was significantly higher in defenders than midfielders (P<0.05), and soccer skills were significant lower in goalies than in other positions (P<0.01). The results show significant differences in anaerobic capacity and soccer skills according to position in youth soccer players. Therefore, we suggest that middle and high school soccer players should improve aerobic, an-aerobic capacity, and soccer skills irrespective position to achieve high-level soccer performance.